PENGEMBANGAN e-LKPD BERBASIS ANDROID MENGGUNAKAN KODULAR PADA MATA PELAJARAN MATEMATIKA KELAS VIII DI MTsS PLUS PADANG KANDANG KABUPATEN PADANG PARIAMAN - Rahmi Putri Ayunda; Supratman Zakir; Zulfani Sesmiarni; Wedra Aprison (Universitas Pahlawan Tuanku Tambusai, 2023)
Based on the results of the researcher's interview with the Mathematics teacher for class VIII at MTsS Plus Padang Kandang. Although whiteboard media is still used, technology users have begun to be applied to support the learning process. However, it is not optimal in helping reduce students' learning difficulties. The main learning resource is books and delivering material using the lecture method. Learning media has not used Android technology to accommodate the needs of students. This research is to produce learning e-LKPD application products using Kodular in Mathematics class VIII MTsS Plus Padang Kandang that are valid, practical and effective for use in learning. The type of research that researchers use is research and development (Research and Development) or abbreviated as R&D. The R&D model used in this research is the 4D version (Define, Design, Develop and Disseminate). While the development of learning applications uses the Luther-Sutopo model which consists of Concept, Design, Material Collecting, Assembly, Testing and Distribution. Based on the results of the research that has been done, it can be concluded that the resulting application can be utilized and is suitable for use as a support for the learning process in Mathematics. The results of the validity test by experts on Mathematics e-LKPD are categorized as valid with an average value of 0.84. The media e-LKPD practicality test shows the result that the media has very high practicality with a value of 0.85. Meanwhile, the e-LKPD effectiveness test shows that it has a high level of effectiveness with a value of 0,74. Keywords: e-LKPD, Kodular, Mathematic, android